Global trends and regional disparities in the burden of headache disorders, 1990–2021: a comprehensive analysis of the global burden of disease study - Rui, Yuanyuan; Wu, Bing; Li, Qian; Zhang, Kai (Frontiers in Neurology, 2025)
BackgroundHeadache disorders significantly impact health and functioning, yet studies on their global burden across all age groups are limited. This study utilizes data from the Global Burden of Disease (GBD) 2021 to investigate the global burden of headache disorders.MethodsThis analysis draws on GBD 2021 data, covering 204 countries and territories. We investigated the prevalence, incidence, and DALYs for headache disorders from 1990 to 2021, calculating Estimated Annual Percentage Change (EAPC) to analyze temporal trends. Additionally, decomposition analysis was used to evaluate the contributions of aging, population growth, and epidemiological changes. The slope index of inequality and concentration index were employed to assess inequalities in disease burden.ResultsFrom 1990 to 2021, the global prevalence of headache disorders increased significantly, reaching approximately 2.81 billion cases in 2021, a 57.16% increase from approximately 1.79 billion cases in 1990. During this period, the global Age-Standardized Prevalence Rate (ASPR) and Age-Standardized DALY Rate (ASDR) both showed gradual increases, while the Age-Standardized Incidence Rate (ASIR) remained stable, with EAPC values of 0.01, 0.04 and-0.0002, respectively. High Socio-demographic Index (SDI) regions exhibited the highest rates of ASPR, ASIR, and ASDR, whereas Middle SDI regions experienced the fastest growth, with EAPC values of 0.17, 0.17, and 0.18, respectively. The SDI exhibited significant positive correlations with the EAPC of ASPR (R = 0.18, p = 0.0093) and ASIR (R = 0.16, p = 0.027). Decomposition analysis identified population growth as the primary driver in regions with increasing disease burden. The slope index of inequality (SII) shows that disparities in ASPR, ASIR, and ASDR slightly increased from 7,648.13, 2,506.76, and 88.45 in 1990 to 7,851.55, 2,557.94, and 100.38 in 2021. In contrast, the concentration index (CI) in 2021 were 0.05, 0.05, and 0.04, showing no significant change from 1990.ConclusionHeadache disorders continue to impose a growing burden globally, with marked regional and socio-economic disparities. Addressing these trends requires targeted public health interventions, particularly in high-burden and low-resource settings.